2020
DOI: 10.1177/0957650920947845
|View full text |Cite
|
Sign up to set email alerts
|

Loss analysis of the shrouded radial-inflow turbine for compressed air energy storage

Abstract: The shrouded radial-inflow turbine is widely employed as a power generation device in the compressed air energy storage (CAES) system. The loss mechanism and off-designed performance of the shrouded radial turbine are lesser known hitherto and should be deeply understood. Loss analyses of a shrouded radial turbine are conducted numerically based on the first and second laws of thermodynamics in the current study. The relationship between losses and the secondary flow has been discussed in detail. A high propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Shao et al. 22 further investigated the shroud-casing leakage flow in a shrouded radial-inflow turbine for CAES system. It can be found that the wake and leakage vortex related to the case-shroud leakage flow generated primary flow loss in the outlet region of rotor, the detailed results can be observed in Figure 11.…”
Section: Progress On Leakage Flow In the Radial Inflow Turbine Of Caes Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Shao et al. 22 further investigated the shroud-casing leakage flow in a shrouded radial-inflow turbine for CAES system. It can be found that the wake and leakage vortex related to the case-shroud leakage flow generated primary flow loss in the outlet region of rotor, the detailed results can be observed in Figure 11.…”
Section: Progress On Leakage Flow In the Radial Inflow Turbine Of Caes Systemmentioning
confidence: 99%
“…As mentioned in reference, 22 although the case-shroud leakage flow leakage flow only performed a disturbance at outlet of rotor, its negative effect on isentropic efficiency can not be neglected. Therefore, further investigation on the case-shroud leakage flow reduction of CAES radial-inflow turbine is conducted.…”
Section: Progress On Leakage Flow In the Radial Inflow Turbine Of Caes Systemmentioning
confidence: 99%